Penerapan Model PBL untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V MI Swasta - Nur Hikmah; Minnah El Widdah (STIKes Ibnu Sina Ajibarang, 2025)
This thesis discusses the use of problem based learning (PBL) models in natural and social science (IPAS) subjects to improve student learning outcomes in class V of private Islamic elementary schools in Tarbiyah Islamiyah Jelutung, Jambi City in 2024/2025. This study uses classroom action research (PTK) by implementing II cycles or action rounds. Data collection techniques in this study use planning, observation, documentation, test and non-test instruments in learning using the problem based learning (PBL) model. The results of this study indicate that there is an increase in student learning outcomes in natural and social science (IPAS) learning using the problem based learning (PBL) model, this is evidenced by the increase in the percentage of test results from cycle I and cycle II. In the pre-cycle, namely 29.41%, cycle I, namely 47% of students who completed this had not reached the percentage of completeness, and continued with cycle II, namely 76% of students who completed had met the completeness. The findings of this study state that by implementing the problem based learning (PBL) model, it can improve student learning outcomes in natural and social science (IPAS) subjects with the material Harmony and Ecosystems.